USE OF INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Nuriddinov Khojiakbar (Academia Science Repository, 2023)
"The priority policy of the Republic of Uzbekistan is to democratize the work content of the educational system and to educate the youth of the 21st centu-ry into comprehensively developed, mature, worldly-minded, educated, well-rounded individuals in accordance with world education standards." 79. The cur-rent issues of education and pedagogy include the purpose and essence, content, and methods of education based on the use of advanced modern technical achievements, as well as issues of scientific provision for the organization of the process. Pedagogical technology has different characteristics depending on the content. Also, every pedagogue is involved in the process of education and up-bringing.